2020
DOI: 10.1001/jamanetworkopen.2020.2769
|View full text |Cite
|
Sign up to set email alerts
|

Association of Primary Intracerebral Hemorrhage With Pregnancy and the Postpartum Period

Abstract: IMPORTANCE Intracerebral hemorrhage (ICH) during pregnancy and the postpartum period results in catastrophic maternal outcomes. There is a paucity of population-based estimates of pregnancyrelated ICH risk, including risk during the extended postpartum period. OBJECTIVE To evaluate ICH risk during pregnancy and an extended 24-week postpartum period in a population-level cohort and to determine fetal and maternal outcomes as well as demographic and comorbidity factors associated with ICH during pregnancy and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…In addition to the increased risk of spontaneous ICH in patients with COVID-19, pregnancy itself can be considered as a risk factor for nontraumatic ICH. about which, Meeks et al demonstrated an increased rate of ICH during the third trimester and the first 12 postpartum weeks [ 13 ]. Data from previous studies demonstrated an increase in the risk of ICH in pregnant women with eclampsia, gestational hypertension, coagulopathy, and history of tobacco use by increasing the states of cerebral hyper-perfusion [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the increased risk of spontaneous ICH in patients with COVID-19, pregnancy itself can be considered as a risk factor for nontraumatic ICH. about which, Meeks et al demonstrated an increased rate of ICH during the third trimester and the first 12 postpartum weeks [ 13 ]. Data from previous studies demonstrated an increase in the risk of ICH in pregnant women with eclampsia, gestational hypertension, coagulopathy, and history of tobacco use by increasing the states of cerebral hyper-perfusion [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…about which, Meeks et al demonstrated an increased rate of ICH during the third trimester and the first 12 postpartum weeks [ 13 ]. Data from previous studies demonstrated an increase in the risk of ICH in pregnant women with eclampsia, gestational hypertension, coagulopathy, and history of tobacco use by increasing the states of cerebral hyper-perfusion [ 13 ]. However, we observed none of these factors in this case.…”
Section: Discussionmentioning
confidence: 99%
“…42 43 This may be related to an increased circulating volume, presence of pre-existing cranial vascular anomalies, coagulopathy or hypertensive disorders such as preexisting hypertension and pre-eclampsia/eclampsia. [42][43][44] The effect of a neuraxial block on the risk of intracranial bleeding in pregnant or direct postpartum women is unknown.…”
Section: Pathophysiologymentioning
confidence: 99%
“…What may be less well recognized is the more immediate short‐term risk following a pregnancy with HDP. About 6% of maternal deaths are caused by HDPs, 5 and they may contribute to cerebrovascular and other cardiovascular deaths as well 6 . More importantly, 60% of these deaths occur in the first 6 weeks postpartum 7 .…”
Section: Featured Reviewsmentioning
confidence: 99%